Multiple scattering of slow muons in an electron gas - Archubi, Claudio Darío (2017)
Abstract: A comparative study of the angular dispersion of slow muons in an electron gas is performed using three dielectric models which represent the case of metals (Lindhard model for a free electron gas) and the cases of semiconductors and insulators (Levine and Louie model and Brandt and Reinheimer model for systems with a band gap) and a non-linear model for both cases at very low velocities. The contribution of collective electronic excitations according to the dielectric model are found to be negligible. The results from the calculation using Lindhard expressions for the angular half width are coincident with the result of a multiple scattering model. In particular, the effects produced by the band gap of the material are analyzed in detail. Finally, as the recoil effect is negligible, there is an almost exact scaling, for a given velocity, between the proton and the muon results. Graphical abstract: [Figure not available: see fulltext.].